El mtodo analtico y la importancia de la tica y la poltica para la convivencia en estudiantes de educacin secundaria - Mundaca Gonzales, Neyver Mesias (2019)
The learning session is entitled analytical method and the importance of the ethics and the student coexistence policy in students of secondary education, Which Was performed as part of the Personal, Civic and citizenship development area, for fifth grade students of secondary education in San Nicols school._x000D_ The purpose of the lesson, the analysis and assessment of the ethics and coexistence policy was obtained by using the analytical method and its respective strategies. The information and thematic field were friended using the theoretical contributions of the mast important Greek philosophers and the pedagogical contribution of Paulo Freire